Al-Jadal al-Kalāmī Bayn Nahḍah al-Ulamā’ wa al-Wahhābiyah fī ‘Facebook’: Ṣafhah ‘Abd al-Wahhāb Ahmad Namūdzajan: The Theological Debate between Nahdatul Ulama and Wahhabi on Facebook: An Analysis of Abdul Wahab Ahmad - Ryandi Ryandi (University of Darussalam Gontor, Indonesia, 2023)
The article discusses the struggle for the “Aswaja theological authority” between the Nahdatul Ulama (NU) and Wahhabi groups on Facebook. This article records how the forms, issues and shifts of the discourse. The study was carried out by observing young NU elite accounts who actively criticized Wahhabi theology on facebook. Data analysis uses discourse analysis. The study found that the struggle for the